Experimental Investigation of Pressure Fluctuations for Centrifugal Pumps at Different Rotational Speed - TAN Linwei;NIU Guoping;SHI Weidong;SHI Zhouhao;CHEN Cheng (Nantong Daxue xuebao. Ziran kexue ban)
The pressure fluctuations of the centrifugal pumps have a great influence on the safe and stable operation of centrifugal pumps. In order to reveal the pressure fluctuations characteristics of the centrifugal pump at different rotational speed, a single-blade centrifugal pump is used as the test pump and the pump performance is obtained. The high-frequency pressure fluctuations sensor is used to measure the pressure fluctuations of the pump at different rotational speed. The pump performance test results show that the H-Q curves at different rotational speed are basically parallel, which is consistent with similar conversion. The pressure fluctuations test results show that the pressure fluctuations in the volute gradually weaken from the tongue along the direction of the impeller rotation, and the pressure fluctuations intensity is the smallest near the design flow condition. The frequency domain analysis shows that the dominant frequency is the impeller rotational frequency fn, but there is also a significant broadband signal in the range of 5 fn. Pressure fluctuations intensity decreases remarkably with the decrease of the rotational speed, and the pressure fluctuations intensity does not completely match the similar conversion of the rotational speed. The higher the rotational speed, the stronger the potential flow interaction of the volute and impeller, also the stronger the pressure fluctuations periodicity. And the wake interaction is obvious at low flow rate and low rotational speed, thus the pressure fluctuations become more complicated and the periodicity becomes weaker at low flow rate and low rotational speed.